Evaluation and selection of suppliers under multi-product purchase based on fuzzy multi-objective integer programming model - Ling Hu; Zhuangpin Wei (Chinese Control and Decision Conference, 2014)
Suppliers evaluation and selection is one of the most critical activities of purchasing management in a supply chain, because of the key role of suppliers' performance in achieving the objectives. And it is a multi-criteria decision-making in which the objectives are not equally important. Supplier evaluation and selection decisions are complicated by the fact that various criteria must be considered in the decision-making process for the decision makers. In this paper, vagueness and imprecision of the objectives, constraints and parameters are considered, and the fuzzy multi-objective integer programming model is proposed to solve suppliers selection problem under multi-product purchases.